Use of a carbon paste electrode modified with spinel-type manganese oxide as a potentiometric sensor for lithium ions in flow injection analysis - Teixeira, MFS; Cavalheiro, ETG; Bergamini, M. F.; Moraes, F. C.; Bocchi, N. (Wiley-Blackwell, 2004)
A potentiometric sensor constructed from a mixture of 25% (m/m) spinel-type manganese oxide (lambda-MnO2), 50% (m/m) graphite powder and 25% (m/m) mineral oil is used for the determination of lithium ions in a flow injection analysis system. Experimental parameters, such as pH of the carrier solution, flow rate, injection sample volume, and selectivity for Li+ against other alkali and alkaline-earth ions and the response time of this sensor were investigated. The sensor response to lithium ions was linear in the concentration range 8.6 x 10(-5) - 1.0 x 10(-2) mol L-1 with a slope 78.9 +/- 0.3 mV dec(-1) over a wide pH range 7 - 10 (Tris buffer), without interference of other alkali and alkaline-earth metals. For a flow rate of 5.0 mL min(-1) and a injection sample volume of 408.6 muL, the relative standard deviation for repeated injections of a 5.0 x 10(-4) mol L-1 lithium ions was 0.3%.
Keywords: potentiometric sensor; lambda-manganese oxide; lithium ions; flow injection analysis